Isolation and identification of the fungi that cause rotting of fruits and vegetables found in the markets of Basra city (Eurasian Medical Research Periodical, 2022)
This study aims to focus on isolating and diagnosing the fungi that cause fruit and vegetable damage in the city of Basra and identifying the types of fungi that cause fruit rot, which affects agricultural production and reduces production quantities. This study also aims to reduce the economic losses in fruits and vegetables due to the attack of microorganisms including fungi on fruits and vegetables. 10 types of fungi were isolated from infected fruits and vegetables in the city of Basra and displayed in the local markets The aim. of the study to identify mold-causing fungi in fruits and vegetables